2018
DOI: 10.1155/2018/3064046
|View full text |Cite
|
Sign up to set email alerts
|

Liver Retraction Using n-Butyl-2-Cyanoacrylate (NBCA) Glue during Laparoscopic Splenectomy and Azygoportal Disconnection in Cirrhotic Patients

Abstract: Background Although liver retraction using n-butyl-2-cyanoacrylate (NBCA) glue has been applied to laparoscopic upper abdominal surgery in noncirrhotic patients, there is still no consensus on its safety and feasibility for cirrhotic patients. In this study, we aimed to investigate the safety and effectiveness of liver retraction using NBCA glue during laparoscopic splenectomy and azygoportal disconnection (LSD) for gastroesophageal varices and hypersplenism secondary to liver cirrhosis and portal hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Some papers have reported that NBCA is biodegradable, biocompatible, nontoxic, and used in some clinical applications. (Jang et al, 2017;Kong et al, 2018;Sugawara et al, 2019). N,N 0 -(Sulfonyldi-4,1-phenylene)bis(2-chloroacetamide) (TC-E-5003) is a selective protein arginine methyltransferase 1 (PRMT1) inhibitor (IC 50 ¼1.5 lM).…”
Section: Introductionmentioning
confidence: 99%
“…Some papers have reported that NBCA is biodegradable, biocompatible, nontoxic, and used in some clinical applications. (Jang et al, 2017;Kong et al, 2018;Sugawara et al, 2019). N,N 0 -(Sulfonyldi-4,1-phenylene)bis(2-chloroacetamide) (TC-E-5003) is a selective protein arginine methyltransferase 1 (PRMT1) inhibitor (IC 50 ¼1.5 lM).…”
Section: Introductionmentioning
confidence: 99%
“…22 This study was mainly based on the clinical manifestations of patients before and after surgery, such as bleeding, liver function, hepatic encephalopathy, etc., to observe the benefits of operation by self-control. [23][24][25][26] Both domestic and foreign reports have shown that the incidence of hepatic encephalopathy after shunting is not high. The rate in the report of Johnson et al 27 was 9.6%, and in a domestic report Zhen et al 28 cited that the incidence of hepatic encephalopathy was 2.5% and 4.1% respectively in 5 and 10 years after devascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiences, we proposed the use of n-butyl-2-cyanoacrylate glue (NBCA) to fix the thick “protrusion” of the liver leaf surface to the liver surface during LC. [ 6 ] The procedure contributes to the visualization of the gallbladder triangle. In this study, we aim to investigate the safety and effectiveness of NBCA as a means of fixing a thick “protrusion” on the square leaf surface of liver in LC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these methods are not suitable for the thick “protrusion” retraction of liver leaf surface. In our experiences, we proposed the use of n-butyl-2-cyanoacrylate glue (NBCA) to fix the thick “protrusion” of the liver leaf surface to the liver surface during LC [6] . The procedure contributes to the visualization of the gallbladder triangle.…”
Section: Introductionmentioning
confidence: 99%